Candide : or, Optimism - Voltaire, 1694-1778.; Butt, John Everett (London ; New York : Penguin Books, 1947)
It was the indifferent shrug and callous inertia that this 'optimism' concealed which so angered Voltaire, who found the 'all for the best' approach a patently inadequate response to suffering, to natural disasters - such as the recent earthquakes in Lima and Lisbon - not to mention the questions of illness and man-made war. Moreover, as the rebel whose satiric genius had earned him not only international acclaim, but two stays in the Bastille, flogging and exile, Voltaire knew personally what suffering involved. In Candide he whisks his young hero and friends through a ludicrous variety of tortures, tragedies and reversals of fortune, in the company of Pangloss, a 'metaphysico-theologo-cosmolo-nigologist' of unflinching optimism. The result is one of the glories of eighteenth-century satire.
How Candide was brought up in a beautiful country house, and how he was driven away -- What happened to Candide amongst the Bulgars -- How Candide escaped from the Bulgars, and what happened to him afterwards -- How Candide met his old tutor, Dr. Pangloss, and what came of it -- Describing tempest, shipwreck, and earthquake, and what happened to Dr. Pangloss, Candide, and James, the Anabaptist -- How a magnificent auto-da-fe was staged to prevent further earthquakes, and how Candide was flogged -- How an old woman took care of Candide, and how he found the lady he loved -- Cunegonde's story -- Relating further adventures of Cunegonde, Candide, the Grand Inquisitor, and the Jew -- Describing the distressing circumstances in which Candide, Cunegonde, and the old woman reached Cadiz, and how they set sail for the new world -- Old woman's story -- Old woman's misfortunes continued -- How Candide was forced to leave the lovely Cunegonde and the old woman -- Reception Candide and Cacambo met with from the Jesuits of Paraguay -- How Candide killed the brother of his beloved Cunegonde -- Adventures of our two travellers with two girls and two monkeys, and what happened to them amongst the savage Oreillons -- How Candide and his servant reached the country of Eldorado and what they saw there -- What they saw in the country of Eldorado -- What happened to them at Surinam, and how Candide made the acquaintance of Martin -- What happened to Candide and Martin at sea -- What Candide and Martin discussed as they approached the coast of France -- What happened to Candide and Martin in France -- Candide and Martin reach the coast of England, and what they see there -- About Pacquette and Brother Giroflee -- Visit to Count Pococurante, a noble Venetian -- How Candide and Martin supped with six strangers, and who they were -- Candide's journey to Constantinople -- What happened to Candide, Cunegonde, Pangloss, Martin, and the rest -- How Candide found Cunegonde and the old woman once more -- Conclusion.
Keywords: French fiction -- 18th century -- Translations into English; Satire, French -- Early works to 1800.; France -- Politics and government -- Satire -- 18th century